Tony Allen An Autobiography of the Master Drummer of Afrobeat - Allen, Tony; Veal, Michael E. (Duke University Press, 2013)
Tony Allen is the autobiography of legendary Nigerian drummer Tony Allen, the rhythmic engine of Fela Kuti's Afrobeat. Conversational, inviting, and packed with telling anecdotes, Allen's memoir is based on hundreds of hours of interviews with the musician and scholar Michael E. Veal. It spans Allen's early years and career playing highlife music in Lagos; his fifteen years with Fela, from 1964 until 1979; his struggles to form his own bands in Nigeria; and his emigration to France.Allen embraced the drum set, rather than African handheld drums, early in his career, when drum kits were relatively rare in Africa. His story conveys a love of his craft along with the specifics of his practice. It also provides invaluable firsthand accounts of the explosive creativity in postcolonial African music, and the personal and artistic dynamics in Fela's Koola Lobitos and Africa 70, two of the greatest bands to ever play African music